HUBUNGAN PELAYANAN PERAWAT DENGAN TINGKAT KEPUASAN PASIEN DI UGD RS AWAL BROS PEKANBARU - Fatkhul Muhlisin; Bayhakki Bayhakki; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
The cutting edge in health care is a nurse, where nursing is a profession that often interact with the patient, so the patient satisfaction is largely influenced by how good the quality of nursing care that is given. This study aimed to determine the correlation between nursing care and patient satisfaction level in the Awal Bros Hospital Pekanbaru. The design study was descriptive correlation with cross-sectional study. The research sample was 100 people who were taken based on inclusion criteria using accidental sampling approach. The results of this study showed that the majority of research subjects was the category of adult and elderly in each 39 respondents (39%),male were 58 respondents (58%). Majority of their education were higher education  with the number of 39 respondents (39%) and elementary school as much as 15 respondents (15%). Patients with outpatient status 60 respondents (60%) and inpatients as many as 40 respondents (40%). Test results chi-square was showed p value ( 0.000) <α (0.05) so it was concluded there was a correlation between nurse care and satisfaction level of patients in the Awal Bros Hospital Pekanbaru. Good service will always be directly proportional to the level of patient satisfaction. Awal Bros Hospital is expected to improve the standard and quality of patient satisfaction so as to create a positive impact for patients, health professionals and health services.  Keyword: Emergency Unit, nursing care, patient satisfaction